Sei innovativ und werde Intrapreneur (Assemble You, 2022)
Welcome to our Assemble You Learning Podcast. You may think it's a better idea to just dive headfirst into the world of entrepreneurship. If you have the necessary network and a brilliant idea, why not start your own business, right? Being an entrepreneur is good. However, if you have more than one brilliant idea, or would rather focus on a specific product or structure, intrapreneurship might be even better. On the one hand you can concentrate on your ideas, on the other hand you get the resources to develop your ideas. But you can also sell yourself as an innovator and highlight your skills in this area. Today, any good company realizes that competitiveness and innovation are essential to stay relevant. As an intrapreneur, if you can sell these skills, you will always be in demand. Learning Objectives Learn the three key elements of an intrapreneur Learn about some of the most successful and innovative intrapreneurs in history.